Implementation of Meranti Islands Regional Government Responsibilities towards ODGJ in Independent Efforts Based on PP 28/2024 and Law 17/2023 concerning Health and Islamic Legal Perspectives - Widya Nengsih; Ardiansah, Ardiansah; ⁠Indra Afrita (al-Afkar, Journal For Islamic Studies, 2025)
This study analyzes the implementation of the responsibility of the Regional Government of Kepulauan Meranti in supporting the independence of Persons with Mental Disorders (ODGJ), based on Government Regulation No. 28 of 2024 as the implementing regulation of Law No. 17 of 2023 on Health, with additional insights from the perspective of Islamic law. The research applies a qualitative approach through in-depth interviews, field observations, and document analysis. The findings reveal that the regional government, through the local Health Office, Social Affairs Office, and Regional General Hospital, has initiated various mental health programs. However, these efforts still encounter significant challenges, such as the shortage of professional mental health workers, limited budget allocation, and geographical barriers of the archipelagic region that hinder service accessibility. Another pressing issue is the limited capacity of families to provide adequate care for ODGJ. Existing initiatives include primary-level mental health services and cross-sector coordination, yet their effectiveness remains suboptimal. From the perspective of Islamic law, ensuring the rights and protection of ODGJ is a moral and social obligation of the government in realizing public welfare (maslahah). Therefore, this study recommends strengthening regulations that prioritize the rights of ODGJ, enhancing cross-sectoral collaboration, and utilizing local potential to sustainably expand the reach of mental health services, in line with both positive law and Islamic legal values.